Comparative degradation between heavy and light crude oil mediated by nitrogen‐induced cell‐surface hydrophobicity - Wong, Kok Kee; Hamzah, Ainon (wILEY, 2018)
A bacterial strain UKMP‐10M2 isolated from a Malaysian petroleum refinery was able to degrade 84% of heavy Khafji sour crude and 68% of light Tapis sweet crude within seven days. Analysis of gas chromatography‐flame ionization detector chromatograms show the strain UKMP‐10M2 degraded up to 90% pristane and 50% phytane in heavy crude, but significantly lower pristane (50%) and phytane (30%) were degraded from the light crude. A mixture of aliphatic hexadecane and three‐ring phenanthrene better supported the growth of isolate UKMP‐10M2 compared to using phenanthrene alone, suggesting cometabolism influenced how crude oil with different individual hydrocarbon contents affected the degradation. Peptone as the source of nitrogen increases the emulsifying index in UKMP‐10M2 exposed to heavy Khafji sour crude 20% higher than in light Tapis sweet crude. However, BATH assay showed the same nitrogen source increases bacterial cell surface hydrophobicity of UKMP‐10M2 up to 14% higher in light Tapis crude oil compared to heavy Khafji. This study suggest the nitrogen source plays a decisive role in elevating UKMP‐10M2 bacterial cells hydrophobicity, and in correlation with types of crude oil. Phylogenetic tree analysis based on 16S rDNA sequence results identified the strain to be Rhodococcus ruber.